Clinical utility of cerebrospinal fluid-placental alkaline phosphatase for the diagnosis of intracranial germinoma - Satoshi Obu; Katsutsugu Umeda; Kougoro Iwanaga; Satoshi Saida; Itaru Kato; Hidefumi Hiramatsu; Yohei Mineharu; Yoshiki Arakawa; Megumi Uto; Takashi Mizowaki; Souichi Adachi; Tomoo Daifu; et al. (Elsevier, 2022)
The clinical utility of measuring cerebrospinal fluid placental alkaline phosphatase (CSF-PLAP) was evaluated in three patients with germinoma. CSF-PLAP was elevated in two patients with suprasellar germinoma who were symptomatic before developing typical radiological findings. The third patient, who had been radiologically diagnosed with a pineal mature teratoma, was suspected of having a germinoma component due to elevated CSF-PLAP; this patient received adjuvant radiochemotherapy. The presence of a germinoma-specific tumor marker may aid in the early diagnosis of suspicious cases at initial clinical presentation and in the accurate subtype classification of intracranial germ cell tumors.